2022
DOI: 10.3389/fnmol.2022.1069940
|View full text |Cite
|
Sign up to set email alerts
|

TrkB signaling is correlated with muscular fatigue resistance and less vulnerability to neurodegeneration

Abstract: At the neuromuscular junction (NMJ), motor neurons and myocytes maintain a bidirectional communication that guarantees adequate functionality. Thus, motor neurons’ firing pattern, which is influenced by retrograde muscle-derived neurotrophic factors, modulates myocyte contractibility. Myocytes can be fast-twitch fibers and become easily fatigued or slow-twitch fibers and resistant to fatigue. Extraocular muscles (EOM) show mixed properties that guarantee fast contraction speed and resistance to fatigue and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 108 publications
1
1
0
Order By: Relevance
“…There were not significant alterations in the integrity of NMJs, although they were generally smaller in Bdnf f/f ; HSA-Cre mice ( Delezie et al, 2019 ). This role of BDNF in FF physiology is consistent with the observations that BDNF, NT4, TrkB and phosphorylated TrkB (p-TrkB) are all higher in fast muscles, such as extensor digitorus longus (EDL) muscles and tibialus anterior (TA) muscles, as compared to soleus (slow) muscles ( Just-Borras et al, 2022 ). The examination of whether TrkB is required for maintenance of motor neurons and their NMJs was evaluated in Trkb +/− mice in which the TrkB dosage was reduced by 50% ( Kulakowski et al, 2011 ).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…There were not significant alterations in the integrity of NMJs, although they were generally smaller in Bdnf f/f ; HSA-Cre mice ( Delezie et al, 2019 ). This role of BDNF in FF physiology is consistent with the observations that BDNF, NT4, TrkB and phosphorylated TrkB (p-TrkB) are all higher in fast muscles, such as extensor digitorus longus (EDL) muscles and tibialus anterior (TA) muscles, as compared to soleus (slow) muscles ( Just-Borras et al, 2022 ). The examination of whether TrkB is required for maintenance of motor neurons and their NMJs was evaluated in Trkb +/− mice in which the TrkB dosage was reduced by 50% ( Kulakowski et al, 2011 ).…”
Section: Introductionsupporting
confidence: 89%
“…TrkB.T1 typically acts in an inhibitory fashion to suppress TrkB signaling, and this splice variant is also deleted in Trkb f/f ; Vacht -Cre mice. Recent studies have indicated that TrkB.T1 is upregulated in peripheral axons and NMJs in Sod1 G93A mice ( Just-Borras et al, 2020 , 2022 ). Furthermore, germline deletion of Trkb.T1 specifically, and not full length Trkb , is neuroprotective in Sod1 G93A mice ( Yanpallewar et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%